Innovative Development of Guided Inquiry-Based Science Learning Materials to Improve Critical Thinking Skills among Junior High School Students - Yudha Irhasyuarna; Fahmi; Hery Fajeriadi; Muhammad Kusasi (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop guided inquiry-based science learning tools to enhance the critical thinking skills of junior high school students on the topic of additive and addictive substances. The research employed a development method using Tessmer’s formative evaluation model, which includes the stages of validation, practicality testing, and effectiveness testing. The developed learning tools consist of lesson plans (RPP), student worksheets (LKPD), and instructional materials. Expert validation results indicated that the tools are in the "highly valid" category, with an average percentage score of 92.5%. The practicality of the tools was reflected in the high implementation of learning activities, ease of use by teachers, and positive student responses. Effectiveness testing showed a significant improvement in students’ critical thinking skills, with an average N-Gain of 0.49 (moderate category). These findings demonstrate that the guided inquiry-based learning tools are not only theoretically and practically feasible but also have a positive impact on the enhancement of students’ critical thinking skills. Therefore, these tools can serve as an alternative solution for implementing instruction that emphasizes both content mastery and the development of students’ competencies.